Hercules Dome High-Frequency Impulse Ice-Penetrating Radar Data ... - Christian, John; Christianson, Knut; Hills, Benjamin; Hoffman, Andrew; Holschuh, Nicholas; Horlings, Annika; O'Connor, Gemma (U.S. Antarctic Program (USAP) Data Center, 2023)
This dataset contains high-frequency impulse radar data collected at western Hercules Dome in East Antarctica. ...